Signage and Wayfinding Design of DR. H. Kumpulan Pane Regional General Hospital in Tebing Tinggi North Sumatera - Situmorang, Rama Sadrakh; Swasty, Wirania (Universitas Ciputra, 2016)
The General Hospital Dr. H. Kumpulan Pane is a type B hospital with the largest and the most complete facilities compare to other hospitals in Tebing Tinggi, North Sumatera. Signage and wayfinding in this hospital have not been well integrated. There are a lot of signage which is small so that the text and symbol that are unclear, installation of signage are not proper, the color used are not appropriate and typography used are different. Those signage and wayfinding make people difficult to find direction and found the location so that signage have not been effective. This study used field observation, interviews and questionnaires to collect data, as well as comparison matrix to analyze data. The signage design is created by combining text and symbols (pictograms). The theme used is clean, hygienic and simple in accordance with the identity of the characters of the hospital. The shape used on the signage is taken from the shape of the hospital logo and colors taken from the typical icon from North Sumatera namely kenanga flowers and parrots. The color obtained are yellow, black and white, so that the results of signage has its own character. The results are expected to design signage that could help patients and hospital visitors in finding the intended location and improve the services in this Dr. H. Kumpulan Pane Hospital in Tebing Tinggi North Sumatera.